An exploration on the performance of using phase change humidity control material wallboards in office buildings. (15th January 2022) - Zhu, Na; Li, Xingkun; Hu, Pingfang; Lei, Fei; Wei, Shen; Wang, Wentao
Abstract: In this study, a composite double-layer wallboard with shape-stabilized phase change humidity control materials (PCHCM) has been proposed for building usage. This novel PCHCM can absorb/release both heat and moisture to moderate indoor hygrothermal environment. Based on a numerical analysis in an office building in Wuhan (30.52°N, 114.32°E), China, the effects of PCHCM on both building energy consumption and indoor hygrothermal environment has been investigated. Firstly, a simulation model has been developed for the building integrated with PCHCM wallboards in EnergyPlus, combining both heat and moisture transfer finite solution algorithms. After a validation of the model, both heat and moisture transfer characteristics of the proposed composite wallboards were simulated, and its effects on indoor temperature, humidity and building energy consumption were analyzed. The simulation results showed that this novel PCHCM wallboard can effectively improve indoor hygrothermal environment, with reduced energy consumption by about 8.3% in summer and 24.9% in winter, comparing to the actually used materials in the case study building. Highlights: A phase change humidity control material (PCHCM) wallboard was proposed. The double-layer PCHCM wallboard active in summer and winter. Melting temperatures of PCHCM wallboard were optimized. Energy and Hygrothermal performance of PCHCM wallboard are analyzed.